(untitled) (Research, Society and Development, 2020)
Introduction: musicalization is an intervention strategy that seeks to achieve personal development to live better in society and generate the well-being of children with autism, improving cognition, motor skills, perception and socialization. Objective: to point out the therapeutic effects of musicalization in children with autism spectrum disorder. Methodology: an integrative review study where the bibliographic survey was carried out using the following databases: Scielo, LILACS, Kroton’s Scientific Journal Portal and CAPES Journal Portal. Through the keywords: children; music therapy and autism spectrum disorder and derivatives in English children; music therapy and autism spectrum disorder using the Boolean operator “AND” to instrumentalize a search for publications. The inclusion criteria were: experimental articles and clinical cases consistent with the theme of the study, written in Portuguese and English, published between the years 2015 to 2019, available in full free of charge in the online collection. Incomplete articles of articles related to another area of health and incomplete, integrative, systematic, bibliographic or meta-analysis reviews were excluded. Results and Discussion: from the selected descriptors, 198 articles were found, but with an inclusion and exclusion application eliminated 193. In this way, 05 articles were relocated in line with the theme of the study and which met the pre-used tests for analysis and discussion results, being part of the main scope of this work. Conclusion: a song in the form of therapy or as an aid to other forms of treatment, brings relevant results demonstrating how valid a musicalization is in the life of the autistic child, focusing on communication, social interaction, perception and cognitive development.